Efficacy of a Customized Three-Dimensional Printing Surgical Guide for Tibial Plateau Leveling Osteotomy: A Comparison With Conventional Tibial Plateau Leveling Osteotomy - Kim, Jayon; Ko, Jaeeun; Kim, Jaehwan; Seo, Anna; Eom, Kidong (Frontiers in Veterinary Science, 2021)
Objective: To prospectively evaluate the effect of a computed tomography (CT)-based three-dimensional (3D) printing surgical guide on surgical accuracy of tibial plateau leveling osteotomy (TPLO). Study design: Cadaveric study. Animals: Canine cadaveric hindlimbs (n = 14). Methods: TPLO was performed on cadaver hindlimbs disarticulated at the coxofemoral joint to compare and evaluate the conventional TPLO method (n=7) with one that used customized 3D printing surgical guides (n=7). The operation time and postoperative tibial plateau angle (TPA) of the osteotomy were evaluated. Moreover, the osteotomy inclination, torsion, and distance and the direction of eccentricity were assessed using CT reconstruction. Results: Significant differences in the operation time (p<0.001), postoperative TPA (p<0.05), osteotomy inclination (p<0.05), and osteotomy torsion (p<0.05) were observed. Conclusion: The use of TPLO surgical guide reduced the operation time and inaccurate osteotomy. Clinical significance: The surgical technique applied with a customized 3D printing surgical guide could be used to perform osteotomy and TPA adjustment more precisely than conventional TPLO.